CROSS-BORDER MERGERS AND ACQUISITIONS INFLUENCE OF A COMPANY ON WORKFORCE CONTINUITY - Hadinata, Ina Putri Andreana; Utari, Anak Agung Sri (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
The rapid development of multinational companies around the world makes economic progress between countries also get good opportunities supported by processes or mechanisms for a company to always develop and boost its company to become bigger and reach all lines of society, inseparable throughout the world. Therefore, the projected scheme of Mergers and Acquisitions of companies against other companies by reaching companies outside their home country or commonly known as Cross Border Mergers and Acquisitions is widespread. However, behind the processes and mechanisms, there are impacts that must also be considered by a company resulting from the process, namely regarding the continuity of the workforce and employees. The method used in this study is a normative legal research method with specific reference to Indonesian laws and regulations, but still within the scope of discussion of multinational companies on companies from other countries. In this case referring to companies in Indonesia, this method is used as the objective to answer the problems being faced in order to find a proportional solution from the problem. From the results of this study, it can be concluded that the process and mechanism of Cross Border M&A can be carried out but also must pay attention to the legal rules in force in the country of the company that will be merged or acquired so that the company is responsible for any impacts that occur, especially the impact on workforce and employees concerned in order to create a good work system and support for all.